THE EFFECT OF CORPORATE GOVERNANCE COMPLIANCE RATING ON THE COMPANY'S FIRM VALUE: A SURVEY ON MANAGERS' PERCEPTION - ULUSOY, Tolga; SAEED, Mohammed (ASOS Yayinevi, 2022)
In the study evaluating the positive impact of corporate compliance rating on a company's share value, company profitability, and company activity, interviews were conducted with the managers of companies that have very high sales and market shares operating in Istanbul. It is determined that whether the companies are public or not has no difference in terms of corporate governance compliance rating. It is apparent that there is no significant difference between the corporate governance compliance ratings of public and non-public companies in terms of company profitability. Therefore, it is determined that whether the companies are public or not has no significant difference in the corporate governance compliance rating. It is evident that the corporate governance compliance ratings of public and non-public companies do not have a positive effect on company activities. Accordingly, it can be stated that whether the companies are public or not, a corporate governance compliance rating does not have a positive effect on company activities. Within the scope of corporate compliance rating, it is determined that the share values, profitabilities, and activities of companies have no significant difference according to the corporate histories of the companies. In terms of compliance with OECD “ Corporate Governance Principles, companies are promised progress in their activities, an increase in their profitability, and maximization of their values in the long run if they strictly adhere to corporate governance compliance policies. Although this study does not represent the general situation, the situation for companies operating with a high scale in Istanbul shows the opposite. In matters such as Compliance with Corporate Governance Principles, Corporate Governance Principles Compliance Rating, and Companies’ inclusion in the Corporate Governance Index, (1) it is accepted that there will be progress in the company's activities, (2) it is accepted that there will be an increase in profitability, albeit slightly, (3) it is considered on the other hand, that there is no effect on issues such as maximizing market values or increasing value of stocks, (4) it is accepted that the primary determinant of market value and stock prices are investors.